“The Perils of Library Instruction”: Contextualizing EdTech's Encroachment on Teaching Through Labour Theory of Value in Academic Libraries - Zvyagintseva, Lydia; Blechinger, Joel (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
In this paper, we argue that the crisis of teaching can be understood as a crisis of labour that continues to impact academic librarians because it is a historical process grounded in larger socio-political shifts precipitated by capitalism. We demonstrate that the emergence and development of teaching—and specifically teaching information literacy (IL) as a kind of librarian curriculum—in academic libraries in North America corresponds to the emergence of neoliberalism. The shocks created by neoliberal fiscal austerity along with anxiety about de-professionalization and de-skilling provoked by cheaper and more widely available information technology created a mounting crisis of legitimacy in librarianship throughout the late 1970s and into the 1980s. Librarians ostensibly remedied this crisis through the positioning of IL as a central contribution of the profession to the academy and society. The COVID-19 pandemic and economic recessions have only intensified the proletarianization processes that have been ongoing since the 1970s. As teaching, learning, and assessment technologies proliferate in the academy, librarians cannot teach more efficiently to meet the needs of growing university populations. Instead, they must rethink the purpose and goals of librarian teaching in the context of the academy. The question of teaching will not be solved until material conditions of librarian labour in the academy are solved.